Raw water storage as a simple means for controlling membrane fouling caused by inorganic foulants in river water in a tropical region - Takashi Hashimoto (2019)
© 2019 by the authors. Natural waters in tropical countries are turbid and rich in inorganic substances such as iron and manganese. Hence, membrane fouling by these inorganic substances is the most serious problem in membrane filtration processes for potable water production. This study aimed to assess raw water storage as a simple but effective means for controlling membrane fouling in the filtration of river water in a tropical country. Raw water taken from the Ping River in Chiang Mai, Thailand, in different seasons, was either immediately filtered or stored in a tank for two days before filtration through a polyvinylidene difluoride (PVDF) membrane with a nominal pore size of 0.1 μm. The turbidity and particulate organic carbon (POC) in the raw water were reduced by storage, while dissolved manganese was oxidized during the storage period. Although the amounts of metallic substances retained on membranes were larger than those of silica and organic matter, their contribution to the fouling resistance was found to be less than silica and organic carbon. The fouling analysis using hydraulically irreversible fouling index (HIFI) was found to be not able to measure the effects of storage when the initial flux increased. Hence, the ratio of the hydraulically reversible fouling index (HRFI) to the total fouling index (TFI), i.e., HRFI/TFI, was proposed to elucidate the effects of raw water storage on membrane fouling, which was manifest during the early stage of membrane filtration operation.